Structural and functional insights into cellulosomes: masters of plant cell wall degradation - Lindič, Nataša; Vodovnik, Maša (Frontiers in Microbiology, 2025)
Cellulosomes are complex multi-enzyme systems that enable efficient cellulose breakdown in some anaerobic bacteria and fungi. Understanding cellulosome functionality plays a crucial role in expanding their potential for industrial plant biomass degradation and valorization. While knowledge on these intricate structures has been accumulating for several decades, recent insights into their modular architecture, dynamic assembly mechanisms, and potential for synthetic biology-driven redesign for biotechnological applications call for a comprehensive re-evaluation of their structural and functional complexity. This review explores recent advances in understanding these cellulolytic nanomachines, focusing on substrate recognition and binding mechanisms, including the roles of carbohydrate-binding modules and cohesin-dockerin interactions. Cell-surface mechanisms that allow these complexes to attach to and effectively degrade plant biomass are also reviewed. Furthermore, structural adaptations to diverse substrates and environmental conditions are discussed, highlighting the flexibility and the interplay between the cellulosomal components, both catalytic and non-catalytic, and their impact on optimizing cellulose degradation, including carbon source sensing, and its role in modulating cellulosome architecture and activity.